TRANSIVITY ON ELON MUSK’S ONLINE BIOGRAPHY:A SOCIAL ACTORS DISCOURSE ANALYSIS - Anggihat Prasetyoaji (BASIS (Bahasa dan Sastra Inggris), 2020)
This research’s content is the analysis of biography texts about Elon Musk taken from four websites by combining SFL’s transitivity and Leeuwen’s social actor representation approach. The aims of this research are (1) to find the portrayal patterns of the social actor using social actor approach, (2) to find the linguistic evidences of the patterns using transitivity, (3) to explain the portrayal of the social actor based on the patterns found, and (4) to compare the results with the context and genre of biography. This research is categorized as a descriptive-qualitative research by using transitivity and Leeuwen’s social actor approach. Spradely’s method of domain, taxonomy, componential, and cultural context analysis is used to collect and analyze the data. The data sources for this research are four biography texts about Elon Musk taken from Britannica, BBC, Business Insider, and Investopedia. The research produced several results as follows: (1) various social actor representation patterns are used by the writer to convey their intention and stance in relation with the social actor, (2) the processes contained in the texts are identified by using transitivity, thus providing linguistic evidences, (3) representation patterns that are the most consistently occurring are: activation, passivation (subjection and beneficialization), determination, nomination, functionalisation, and instrumentalisation. These patterns can be deduced as the obligatory patterns in biography texts, and (4) the texts analyzed are relevant with the qualities of a biography text.